P20 CARDIOMIOPATHY INDUCED BY ATRIAL FIBRILLATION: WHAT'S BEHIND IT?. (18th May 2022) - Ruffini, S; Astegiano, M; Pasquero, M; Franco, E; Moretti, C
Abstract: Sustained chronic tachyarrhythmias often cause a deterioration of cardiac function known as tachycardiomyopathy. We report the case of a 69 years old male patient, who was sent to the Emergency Department by his general practitioner for worsening dyspnoea and the discovery of previously unknown atrial fibrillation. His personal history included only arterial hypertension in treatment with ARBs, with no family or personal history of coronary artery disease. At a previous echocardiogram performed in 2019, systolic and diastolic functions were normal. The ECG confirmed the diagnosis of atrial fibrillation with rapid ventricular response, and blood chemistry showed a suppressed level of TSH (< 0, 005 mcUI/ml), high FT3/FT4 (4.47 pg/ml/2.34 pg/ml) without any other alterations. A chest X–Ray was normal. The echocardiography evidenced a mildly dilated and hypertrophic left ventricle with severe, global systolic dysfunction, EF 25%, an enlargement of both atria, a mild mitral and tricuspid regurgitation and pulmonary artery mean systolic pressure of 35 mmHg. He was admitted to our Cardiology Department for further investigations. The patient was asymptomatic for dyspnoea at rest, only symptomatic with exertion and NYHA III, and hemodynamically stable. A coronarography excluded critical coronary stenosis. We made diagnosis of autoimmune Grave's disease, with multiple not vascularized nodules at echography. In addition to betablockers and diuretics, an appropriate therapy for hyperthyroidism was prescribed, with an improvement of dyspnoea and a reduction of mean cardiac frequency. The patient was discharged with the indication to elective atrial cardioversion, only after thyroid function stabilization. In conclusion, we report a case of a severe systolic dysfunction in an atrial fibrillation induced cardiomyopathy, connected to an unknown thyrotoxicosis in Grave's disease.